P4_5 Piping Hot! - Starkey, David; Nelms, James; Roberts, Declan; Thomas, Suzanne (Physics Special Topics, 2012)
This paper estimates the temperature requirements of an under floor heating system for a room of equal dimensions as those stated in the 2011 paper “Heating a Cold Room”. The temperature of the underwater piping required to maintain 25 Â against heat loss through the walls is calculated explicitly. It is found that for the parameters stated in the paper, the piping must be maintained at 36.9 . The water temperature required for the room heated by 2 radiators is found to be 63.7 .